Design and Construction of a Turbine Pump as Laboratory Scale Micro Hydro Electricity Learning Media - Gunarto; Irawan, Doddy; Julianto, Eko (Universitas Pendidikan Ganesha, 2023)
Lack of understanding of students about renewable energy can be produced from pumps, namely electrical energy. The energy produced by this pump is beneficial for rural areas that do not have electricity. The purpose of this research is to modify the pump as a turbine for a micro-hydro power plant which can be used by students of the Mechanical Engineering Department, the University of Muhammadiyah Pontianak as learning media in the field of fluid machines and laboratory-scale energy conversion machines. The research subjects were 15 students of mechanical engineering and pumps that were converted into turbines to generate electricity. The data collected first comes from the performance test of a pump that has been converted into a pump as a turbine. Further data was obtained from students through a pretest with a conceptual type of pump used as a power plant. Then after the pretest, students were treated by using and operating a pump as a turbine as a learning media. From this media, students must also explain the concept and how the pump as a turbine can produce electrical energy in writing. The student's written results obtained were analyzed to determine the effect of the pump as turbine model on students' understanding of conceptual analysis. The result of this research is a pump that has been converted into a pump as the turbine. In addition, as a simple practical tool to test the performance of the pump as a turbine. There was an increase in students' understanding in terms of the ability to describe the concept of power generation sources from pumps and analyze the process and workings of the pump as a turbine to produce electrical energy.